What is guanxi? a review of definitions. - Phang, Xiao Feng. (2012)
This article aims to address the shortfall in current guanxi literature on its lack of a single primary interpretation. Guanxi (关系) has become a term that is synonymous in understanding Chinese social behavior, yet there is a corresponding lack of research in the psychology discipline. Through examining existing interpretations and definitions of guanxi, recurrent themes were identified from prominent definitions, and then reassembled into a final working interpretation. The recurring themes identified were (a) interpersonal connections, (b) multi-leveled, (c) lack of equivalence in western concepts, and (d) guanxi involves other indigenous Chinese constructs. Evidences of recurrence were presented. Future directions and recommendations in guanxi research were discussed.